Les croisades en Orient. Histoire, mémoires - Abbès Zouache (Tabularia)
This paper aims at studying how the Crusade phenomenon was seen in the East, and its mark on the collective memory. During the twelfth century, the Crusades were gradually understood in its singular way. But it was also considered as an episode of an old confrontation between Islam and Christendom. A memory of the Crusades spread. This memory was mixed with a feeling of aggression and the pride of having resisted through a refocusing on piety and djihad, and through the respect for the established power. After the end of the Crusader states, this memory was enriched with other episodes of the struggle between the Christians and the Muslims. During the Ottoman period, this memory was revived each time the tensions between the Muslims and the Europeans were strong.